The Role Of Camat Communications In Improving The Effectiveness And Work Discipline Of Medan Labuhan District Employees (Pena Cendekia Insani, 2022)
This study aims to determine the role of sub-district communication in improving employee discipline and performance at the Medan Labuhan District Office using the path-goal theory of leadership by Robert House. This research was conducted using qualitative methods. This research activity was conducted at the Medan Labuhan District Office. Data collection techniques using interviews, observation and documentation. The results of this study indicate that the role of communication carried out by the sub-district head in improving the effectiveness and discipline of employees' work is as a leader. The coding of messages carried out by a sub-district head is usually in the form of establishing regulations, ethics, penalties, and provisions in the office and the discursive leadership of the Medan Labuhan sub-district as a leader who supervises several employees who work in the organization he leads, the sub-district head in carrying out his duties and obligations. must be able to work in accordance with the group or employees in the agency.